Dwellings’ Prices in the City of Lublin. Tendencies and Determinants - Kołodziej-Wnuk, Elżbieta (Regional Barometer. Analyses & Prognoses, 2018)
The price of real estate is influenced by a number of factors that provoke huge discrepancies in the prices of separate dwellings. The aim of this study is to conduct a statistical analysis of transactions of the dwellings’ prices on the secondary market in Lublin in the years 2002–2013. The focus is put on the process of transactions’ changes depending on the following criteria: date of transaction, location, technical condition and floor area of dwellings. The relations between above-mentioned factors were analyzed. On the basis of the INSPIRE Directive, the data on the sales and transaction prices of 1 m2 of dwellings are presented using maps of deviations of the average price in the years 2003–2013 with the city’s division into 677 hexagons with the surface of 0,25 ha each.